The construction of the European Union and the need to consolidate a European Communication Politics - Agudiez Calvo, Pinar (CIC. Cuadernos de Información y Comunicación, 2006)
The European Commission prepares a White Paper on a European Communication Policy. Miss Margot Wallström’s, European Commission Vice President and Institutional Relations and Communication Strategy commissioner, exposition demonstrates the problem that European Union suffers from: explaining itself to its citizens. So the first challenge of that White Paper is to build a bridge that invites every important actor in the European Community to break the distance existing between Brussels and the Union citizens, and vice versa. Now it’s noticed that social European Union construction involves necessarily the European demos construction.
Keywords: European Union; European demos; European Communication Policy; Supranationality; Participation; Transparency; European Public sphere